A six-year retrospective study on the causative agents of onychomycosis in China: the emergence of dematiaceous fungi - Ye, Xin; Tian, Jun; Liao, Wanqing; Pan, Weihua; Liu, Zhe; Zhang, Jiaming; Yang, Li; Zhang, Lei (Frontiers in Microbiology, 2025)
IntroductionOnychomycosis, a common nail disease, is caused by a diverse range of pathogens worldwide. However, the epidemiology and pathogen profile of onychomycosis in China remain insufficiently characterized. This study aimed to investigate these aspects in a large Chinese hospital.MethodsA six-year retrospective analysis was conducted at a tertiary hospital in China, where nail samples from 298 patients who were clinically suspected of onychomycosis were cultured and analyzed to identify causative agents and clinical features.ResultsOf the 298 samples, 51.00% (152) were positive for fungal infection. Young adults (18–30 years) comprised the majority of the patients, with a man-to-woman ratio of 1:1.45. Dermatophytes were the most prevalent causative agents (36.18%), followed by yeasts (28.29%) and non-dermatophyte molds (NDMs) (28.29%). Among dermatophytes, Trichophyton species (34.9%) were the most frequently identified, followed by Candida (21.7%) and dematiaceous fungi (8.6%). Dermatophytes were the predominant pathogens in the patients aged 18–50 years. The toenails (63.04%) were more commonly affected than the fingernails (36.96%), with bilateral toenail involvement (34.07%) being the most frequent.ConclusionWhile dermatophytes remain the leading cause of onychomycosis in China, non-dermatophyte molds, particularly dematiaceous fungi, are emerging as significant pathogens. These organisms present unique treatment challenges and warrant increased clinical attention.